Factor Substitution and Factor-Augmenting Technical Progress in the United States: A Normalized Supply-Side System Approach - Klump, Rainer; McAdam, Peter; Willman, Alpo (The Review of Economics and Statistics, 2007)
Using a normalized CES function with factor-augmenting technical progress, we estimate a supply-side system of the U.S. economy from 1953 to 1998. Avoiding potential estimation biases that may have occurred in earlier studies and putting a high emphasis on data consistency, we obtain robust results not only for the aggregate elasticity of substitution but also for the parameters of labor and capital augmenting technical change. We find that the elasticity of substitution is significantly below unity and that technical progress shows an asymmetrical pattern where the growth of labor-augmenting technical progress is exponential, while that of capital is hyperbolic or logarithmic.